Diseño del drenaje pluvial de la localidad de Pilluana provincia de Picota región San Martín - Chavez Iglesias, Alan Angel (2010)
The present project of drainage is a problem of emergency for the health of the District of Piscoyacu, rehearsing waterfall times that lead to optimal points. Design of a city storm drain, comprises the determination of the characteristics of hydraulic, geometric and structural of a sewerage system rain (getting transverse ducts, sections and elevations of the rod for each collector) which leads the runoff product of a storm in the area of influence of a city. With regard to the evacuation of water rain in areas urban is have made records in several cities of the country especially in the Valley of the Cuzco. Work of field, topography, hydrology, coefficients of roughness, the data collection was carried out by initially. Subsequently the results, with the design of the drainage system for the District of Piscoyacu, design cunet hydraulic...